2023
DOI: 10.3390/ijms24032388
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Phylogenetic and Expression Analyses of the PLATZ Gene Family in Medicago sativa L.

Abstract: The PLATZ family is a novel class of plant-specific zinc finger transcription factors with important roles in plant growth and development and abiotic stress responses. PLATZ members have been identified in many plants, including Oryza sativa, Zea mays, Triticum aestivum, Fagopyrum tataricum, and Arabidopsis thaliana; however, due to the complexity of the alfalfa reference genome, the members of the PLATZ gene family in alfalfa (Medicago sativa L.) have not been systematically identified and analyzed. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Members of the same gene family have differences in protein size and complexity. The subcellular localization of the DoWRKY proteins was predicted by using WOLF PSORT, which indicated that most of the DoWRKY proteins were likely located in the nucleus, with only a few in the plasmolemma ( Chang et al, 2022 ; Li et al, 2024 ).…”
Section: Resultsmentioning
confidence: 99%
“…Members of the same gene family have differences in protein size and complexity. The subcellular localization of the DoWRKY proteins was predicted by using WOLF PSORT, which indicated that most of the DoWRKY proteins were likely located in the nucleus, with only a few in the plasmolemma ( Chang et al, 2022 ; Li et al, 2024 ).…”
Section: Resultsmentioning
confidence: 99%